2017
DOI: 10.1002/slct.201701111
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐Assisted Synthesis of C‐4′‐(1,5‐disubstituted)‐triazolespiro‐α‐L‐arabinofuranosyl Nucleosides

Abstract: The synthesis of C‐4′‐(1,5‐disubstituted)‐triazole‐spiro‐α‐L‐arabinofuranosyl nucleosides has been achieved in a regio‐ and stereospecific manner by using intramolecular Huisgen 1,3‐dipolar cycloaddition reaction. The synthesis of these nucleosides necessitates the possession of azide and alkyne moieties in the same molecule, which is being employed as the precursor. Thus, the crucial step in the synthesis of targeted compound is the preparation of 1,2,3‐tri‐O‐acetyl‐5‐azido‐5‐deoxy‐4‐C‐propynyl‐α,β‐L‐arabinof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Puckering amplitude (ν max =59.24), backbone angle (γ=32.88) as well as the torsion describing the anomeric bond (χ=‐171.54) support the inference. The conformational parameters of nucleoside 13 d was found to be comparable with the parent 2′‐ O ,4′‐ C ‐methylene‐α‐L‐ribofuranosyl‐uracil nucleoside monomer ( P =199.67) …”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…Puckering amplitude (ν max =59.24), backbone angle (γ=32.88) as well as the torsion describing the anomeric bond (χ=‐171.54) support the inference. The conformational parameters of nucleoside 13 d was found to be comparable with the parent 2′‐ O ,4′‐ C ‐methylene‐α‐L‐ribofuranosyl‐uracil nucleoside monomer ( P =199.67) …”
Section: Resultsmentioning
confidence: 82%
“…Although, ASOs involving 2′‐ O ,4′‐ C ‐methyleneribofuranosyl‐nucleosides are known for high affinity recognition, their use is also accompanied with the risk of hepatotoxicity . This has persuaded researchers to explore modifications in their scaffold in pursuit of mitigation of the toxic effect while maintaining the antisense activity ,. Among other modifications, methyl substitution at their methylene bridge, i. e .…”
Section: Introductionmentioning
confidence: 99%
“…In order to intramolecular 1,3-dipolar cycloaddition, Prasad and co-workers demonstrated the microwave assisted cyclization of sugar derived azido-alkyne functionality in order to produce triazole appended spiro nucleosides. [181] Intra- Basavaiah et al reported a metal-free high-yielding and convenient synthesis of triazole-fused benzoxazonines 242 starting from Baylis-Hillman-Basavaiah adduct 240 (Scheme 56). [182] Thus, Baylis-Hillman alcohol obtained Scheme 52.…”
Section: Intramolecular Cycloaddition Of Azido-alkyne Precursors Unde...mentioning
confidence: 99%
“…Synthesis of spiro-nucleoside 237 via intramolecular click chemistry from azido-alkyne sugar 233. [181] azides 247 produces the respective triazolo-benzoxazepine scaffolds 248 in moderate yields. The in vitro anticancer activity of novel triazolo-benzoxazepine scaffolds 248 were evaluated against three cancer cells such as Neura 2a (a neuroblastoma cell line), Hep G2 (a liver cancer cell line), and Hek 293 (a kidney cancer cell line) using MTT assay.…”
Section: Intramolecular Cycloaddition Of Azido-alkyne Precursors Unde...mentioning
confidence: 99%
“…In the past few years, our research group has aimed and successfully executed the synthesis of various sugar modified nucleosides following chemical and biochemical pathways. 6′-Methyl-2′-O,4′-C-methylene--L-ribofuranosylpyrimidines, 36 -L-ribofuranosylnucleosides, 37 C-4′spiro-oxetano--L-ribonucleosides 38 were synthesized following chemical pathway, whereas 2′-O,4′-C-methyleneribonucleosides C, 39 C-4′-spiro-oxetanoribonucleosides, 40 homolyxofuranosylpyrimidines D 41 were synthesized following chemoenzymatic pathway. Herein, a facile and efficient methodology has been described for the synthesis of LNA nucleosides 8a,b following a chemoenzymatic pathway (Figure 1).…”
mentioning
confidence: 99%